The Concept of Gender Bias in Islam (Analytical Study) - Wawan Kardiyanto; Fierdha Abdullah Ali (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
According to Islamic juridical norms and international constitutions, justice and equality between men and women have human rights protection for all mankind. From the perspective of figures with a gender perspective, Law no. 1 of 1974 concerning Marriage regulates marriage issues as a type of view and conception that discriminates against women culturally and sociologically. From this explanation, it can be seen that women's laws are still widely debated and considered discriminatory because they are influenced by patriarchal culture, favor women's groups, and do not provide guarantees for women. Injustice treatment of women. Because the Women's law does not protect women in the UUP articles, which is very important to understand by understanding gender analysis.